A multi-control vehicle-to-grid charger with bi-directional active and reactive power capabilities for power grid support. (15th March 2019) - Tan, Kang Miao; Padmanaban, Sanjeevikumar; Yong, Jia Ying; Ramachandaramurthy, Vigna K.
Abstract: This paper proposes a multi-control vehicle-to-grid charger with bi-directional power capability. The proposed charger can perform vehicle battery charging and discharging operations, as well as power grid support such as reactive power compensation, power factor correction, and grid voltage regulation. The performances of the charger controls were examined under various power grid scenarios. Results revealed that the vehicle-to-grid charger attained the highest charger efficiency when operating at unity power factor mode. Nevertheless, vehicle charging at unity power factor introduced a significant grid voltage drop which may violate the grid voltage limits. This problem was solved by using the voltage control, which injected reactive power to the power grid for accurate voltage regulation. This paper also proposed an autonomous multi-control selection algorithm to intelligently switch between the multiple charger controls in response to the power grid condition. Results showed that the proposed algorithm effectively instructed the charger to work in efficient control modes if the grid voltage was within the permissible voltage limits. Whenever the grid voltage exceeded the limits, the charger automatically switched to grid voltage control for power grid voltage regulation. Highlights: Design of multi-control V2G charger for power grid support. Design of V2G charger with bi-directional active and reactive power flow. Develop of control selection algorithm for multiple charger control switching. Technical assessment on V2G charger under various power grid scenarios.